2015
DOI: 10.1007/s00284-015-0954-z
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Bacterial Composition of the Endangered Yangtze Finless Porpoises Living Under Captive and Semi-natural Conditions

Abstract: Intestinal microbiota is essential to the health and physiology of host animals. We undertook the first microbiological study of the fecal bacterial composition from critically endangered (CR) Yangtze finless porpoises (Neophocaena asiaeorientalis asiaeorientalis; YFPs) living under captive and semi-natural conditions using both high-throughput sequencing method and 16S rRNA gene clone library method. As determined by high-throughput sequencing of V3-V4 regions of the 16S rRNA gene, seminatural samples harbore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 61 publications
2
30
2
Order By: Relevance
“…Bray-Curtis distances showed that wild-captured samples clustered on their own while colony and colony-transitional samples clustered together ( Figure 4 a). This is in line with previous studies that show different microbial diversity and community structure in captive vs wild conspecifics [ 28 , 48 , 68 , 69 ]. PLS-DA analysis also indicated separation of wild-captured samples ( Figure 2 a).…”
Section: Discussionsupporting
confidence: 93%
“…Bray-Curtis distances showed that wild-captured samples clustered on their own while colony and colony-transitional samples clustered together ( Figure 4 a). This is in line with previous studies that show different microbial diversity and community structure in captive vs wild conspecifics [ 28 , 48 , 68 , 69 ]. PLS-DA analysis also indicated separation of wild-captured samples ( Figure 2 a).…”
Section: Discussionsupporting
confidence: 93%
“…In previous studies, fecal samples were used to determine the microbiota present in the GI tract of cetaceans 1317 . This was mainly due to the ease of sample collection compared to the invasive procedures required to collect samples from other GI regions.…”
Section: Introductionmentioning
confidence: 99%
“…Sampling locales for the Wuhan Baiji Dolphinarium (WBD; 30°31′28 N, 114°22′58E), Tian e-Zhou Baiji National Nature Reserve (TEZ; 29°51′11 N, 112°35′15E), and Gonghuwan lake for the negative control (31°27′21 N, 120°20′E) are illustrated using a grey circular marker. Map has been modified with permission from Wan et al (2016) time of sampling, the reserve contained a floating net cage (approximately15 × 15 m) with two YFPs being temporarily housed for breeding research. This area was connected to the rest of the oxbow reserve, where approximately 58 other YFPs live.…”
Section: Primer Testing and Optimizationmentioning
confidence: 99%